Effects of confinement reinforcement and concrete strength on nonlinear behaviour of RC buildings - Yon, Burak; Calayir, Yusuf (Techno-Press, 2014)
This paper investigates the effects of confinement reinforcement and concrete strength on nonlinear behaviour of reinforced concrete buildings (RC). For numerical application, an eleven-storey and four bays reinforced concrete frame building is selected. Nonlinear incremental static (pushover) analyses of the building are performed according to various concrete strengths and whether appropriate confinement reinforcement, which defined in Turkish seismic code, exists or not at structural elements. In nonlinear analysis, distributed plastic hinge model is used. As a result of analyses, capacity curves of the frame building and moment-rotation curves at lower end sections of ground floor columns are determined. These results are compared with each other according to concrete strength and whether appropriate confinement reinforcement exists or not, respectively. According to results, it is seen that confinement reinforcement is important factor for increasing of building capacity and decreasing of rotations at structural elements.
Keywords: confinement reinforcement; concrete strength; distributed plastic hinge; nonlinear pushover analysis